2016
DOI: 10.1515/johh-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and lateral soil moisture patterns on a Mediterranean karst hillslope

Abstract: Abstract:The need for a better understanding of factors controlling the variability of soil water content (θ) in space and time to adequately predict the movement of water in the soil and in the interphase soil-atmosphere is widely recognised. In this paper, we analyse how soil properties, surface cover and topography influence soil moisture (θ) over karstic lithology in a sub-humid Mediterranean mountain environment. For this analysis we have used 17 months of θ measurements with a high temporal resolution fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In karst areas, the processes of rainfall in ltration on hillslopes are mainly affected by rainfall characteristics (Gregory et al 2009), vegetation coverage, and soil properties (Canton et al 2016). Rainfall characteristics such as amount, intensity and frequency signi cantly affect the depth of soil water migration (He et al 2012;Yaseef et al 2009).…”
Section: Soil Water Movement Under Light Rainfallmentioning
confidence: 99%
“…In karst areas, the processes of rainfall in ltration on hillslopes are mainly affected by rainfall characteristics (Gregory et al 2009), vegetation coverage, and soil properties (Canton et al 2016). Rainfall characteristics such as amount, intensity and frequency signi cantly affect the depth of soil water migration (He et al 2012;Yaseef et al 2009).…”
Section: Soil Water Movement Under Light Rainfallmentioning
confidence: 99%
“…Fu et al [22] found that soil texture was one of the main influence factors of soil moisture content, which was consistent with the result of this study. Canton et al [30] found that clay content, surface cover had effect on soil moisture on a Mediterranean karst hillslope, and high clay content could explain the increase of soil moisture content. In conclusion, soil texture and natural vegetation cover type could influence each other, such that different vegetation cover types are related to different soil texture and the vegetation cover type could influence soil moisture content by influencing soil texture.…”
Section: Effects Of Different Vegetation Cover Types On Overall Soil mentioning
confidence: 99%
“…Soil moisture plays an important role in the growth of vegetation (Brantley et al 2017;Laio et al 2001). Vegetation can affect soil moisture and its response to precipitation via many complex and interacting hydrological processes (Canton et al 2016;Chen et al 2007;Daly and Porporato 2005;Rivera et al 2014). There are differences in the characteristics of the canopy and root distributions of different vegetation types, and these differences affect the response of soil moisture to rainfall (G ehrels et al 1998).…”
Section: Introductionmentioning
confidence: 99%